Improving Students’ Vocabulary Ability Through Keyword Technique (Action Research at Class XI MIA 2 of SMA Negeri 5 Kendari) - Mclean Hy (Cetta: Jurnal Ilmu Pendidikan, 2019)
This research investigates the improvement of students’ vocabulary ability by applying Keyword Technique at class XI MIA 2 of SMA Negeri 5 Kendari. It aims to find out whether teaching vocabulary by employing the Keyword technique can improve the students’ vocabulary ability or not. This research focuses on solving the students’ problem vocabulary in definition (find out and recognize the meaning of the word) as the major problem in that class based on the preliminary research. This research used a classroom action research (CAR) as a method which requires four stages such as planning, action, observation and reflection. Two cycles are administrated during the application of this research, where each of them consists of three meetings. In collecting data and information, researcher uses some instrument such as field note and vocabulary test. The planned target of this study is 75% of the students can obtain the bench score 75 at minimum. As a result, students’ vocabulary improved after applying keyword as a strategy of learning in the classroom.